ENGLISH LANGUAGE PROFICIENCY ACHIEVEMENT IN 180 HOURS AMONG 2006 BATCH AT UNIVERSITAS ADVENT INDONESIA - Caroline V Katemba; Linda Simarmata; Anne Lou Hendriks (Fakultas Keguruan dan Ilmu Pendidikan Universitas Advent Indonesia, 2011)
Nowadays, English is an official language around the world. Many people have problem forcommunicating because they do not know English. To exceed the problem, it is important tostudy English more and take Test of English as a Foreign Language (TOEFL) because it canhelp them to develop their English ability.The objective of this study is to contribute to this discussion by examining: If there is anysignificant difference in achievement of English language proficiency of the participantsafter taking English for 180 hours during six semesters.The participants were 63 young adult, they were 2006 batch enrolled in Universitas AdventIndonesia. The participants of this study have taken English Entrance Exam (E3in) in the firstsemester and English Exit Exam (E3exit) in the 6th semester.This research obtained the data as follows: X (E3in) as pre-test=63, Y (E3exit) as post-test=63.The means of pre-test was 353.65 with mean standard deviation was 24.488 and with meanstandard error was 3.085. And after the treatments, the mean of post-test was 443.83 with meanstandard deviation was 32.001 and with mean standard error was 4.032. The mean gain scorebetween the two tests was 90.17. This result was supported by t-counted result was 2.636 andt-table result was 1.671. It means that t-counted > t-table. Thus, Ha is accepted, that there is asignificant difference of achievement in English language proficiency after taking English for180 hours during six semesters.